Pengaruh Takaran Pupuk Kandang Sapi dan Pupuk NPK terhadap Pertumbuhan dan Hasil Terung Ungu di Tanah Ultisol - H. Michael Noer Sitorus; Nofia Hardarani; Bambang Fredrickus Langai (Universitas Lambung Mangkurat, 2026)
This study aimed to determine effect of cow manure and NPK Mutiara fertilizer. This research was carried out in the experimental field in the Faculty of Agriculture, University of Lambung Mangkurat from February to April 2022. This study used a completely randomized design (CRD) with 2 types of fertilizers in the form of cow manure (K) and NPK Mutiara fertilizer (N). The cow manure factor consisted of k0 = 5 t ha-1; k1 = 10 t ha-1; k2 = 20 t ha-1. The NPK fertilizer factor consisted of n0 = 200 kg ha-1; n1 = 300 kg ha-1; n2 = 400 kg ha-1. The results indicated that the interaction of cow manure and NPK Mutiara fertilizer had a significant effect on stem diameter at 14 days after planting (DAP). The single factor of cow manure only affected plant height at 35 HST. The single factor of NPK Mutiara fertilizer had a significant effect on stem diameter 35 DAP, number of flowers 63 DAP, harvest age, fruit weight per plant. The single factor of NPK Mutiara fertilizer had a very significant effect on plant height at 35, 42, 49 and 56 DAP, stem diameter at 7, 42, 49 and 56 DAP, number of branches at 42, 49 and 56 DAP, flowering age, number of flowers 56 DAP, the number of fruits per plant and fruit length.